Analysis Development E-Worksheet Based PBL-STEM Approach with a Assisted by Nanofiber Membrane Media on Renewable Energy Materials to Improve Students' Creative Thinking Abilities - Ardi; Ida Sriyanti; Leni Marlina (Postgraduate, University of Mataram, 2025)
The increase in population and global economic growth means that energy demand continues to increase every year, so that limited energy resources such as fossil fuels are depleted more quickly. The purpose of this research is to determine the needs analysis for developing PBL-based e- LKPD with a STEM approach on renewable energy material to improve students' creative thinking abilities. This research is a qualitative descriptive study using a survey through a student needs questionnaire and interviews with physics teachers at Madrasah Aliyah Pondok Pesantren Ahlul Quran Palembang. The data obtained was then analyzed descriptively. The research results show that 80% of students find it difficult to learn renewable energy material. All students and teachers strongly agree if teaching materials are developed in the form of PBL-based e-Worksheetwith a STEM approach so that they can improve students' creative thinking abilities and can be used as teaching materials to support learning by students both at school and independently at home.